1992
DOI: 10.1080/01904169209364495
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and partitioning of biomass and soluble carbohydrates in maize seedlings as affected by source of nitrogen, nitrogen concentration, and cultivar1

Abstract: Seedlings of four maize hybrids were grown hydroponically to investigate the impact of different N sources (Ca(NO 3 ) 2 , (NH 4 ) 2 SO 4 and a 1:1 mixture of both) on (i) production and partitioning of root and shoot dry matter, (ii) concentration of soluble carbohydrates in roots and shoots and their partitioning to these plant parts, (iii) concentration of starch in the shoot, and (iv) N uptake. During the main phase of the experiments (duration 14d), the plants were grown in a greenhouse at 25/22°C day/nigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 29 publications
0
7
0
2
Order By: Relevance
“…To better understand the potential roles of nitrogenous compounds in xylem sap in regulating plant N homeostasis, the amounts of nitrogenous compounds in xylem sap were analyzed, and it was found that N under‐supply decreased nitrate‐ and total N content in xylem sap (Table 1). Since nitrate may serve as a signal to mediate plant N metabolism and development (Crawford and Glass 1998), a nitrate‐N decrease in xylem sap might trigger biological programs that promote carbohydrate allocation from shoots to roots, stimulate root growth, and increase total root length (Henry and Raper 1991; Alfoldi et al 1992; Lopez‐Bucio et al 2003; Hermans et al 2006) (Figure 1B). Due to moderate N oversupply and the enormous buffering capacity of soils (Barber 1995), less effects were derived from HN treatment than that from LN treatment except for a significant increase in total N content in roots (Figure 1A).…”
Section: Discussionmentioning
confidence: 99%
“…To better understand the potential roles of nitrogenous compounds in xylem sap in regulating plant N homeostasis, the amounts of nitrogenous compounds in xylem sap were analyzed, and it was found that N under‐supply decreased nitrate‐ and total N content in xylem sap (Table 1). Since nitrate may serve as a signal to mediate plant N metabolism and development (Crawford and Glass 1998), a nitrate‐N decrease in xylem sap might trigger biological programs that promote carbohydrate allocation from shoots to roots, stimulate root growth, and increase total root length (Henry and Raper 1991; Alfoldi et al 1992; Lopez‐Bucio et al 2003; Hermans et al 2006) (Figure 1B). Due to moderate N oversupply and the enormous buffering capacity of soils (Barber 1995), less effects were derived from HN treatment than that from LN treatment except for a significant increase in total N content in roots (Figure 1A).…”
Section: Discussionmentioning
confidence: 99%
“…The negative consequences of increasing NH 3 rate, and decreasing depth of application or time interval between NH 3 application and planting on maize seedling emergence and early growth development was documented decades ago (Colliver and Welch, 1970a). Reductions in root dry matter were also observed with higher rates of ammonium‐N (NH 4 –N) in studies that involved different forms of N sources (ammonium‐hydroxide, ammonium‐nitrate, ammonium‐sulfate, calcium‐nitrate, potassium‐nitrate), due to higher aqueous NH 3 concentrations (Bennett et al, 1964; Warncke and Barber, 1973; Errebhi and Wilcox, 1990; Alföldi et al, 1992; Schortemeyer and Feil, 1996). The ammonia toxicity may be universal among plant species (Britto and Kronzucker, 2002), but the sensitivity between species (Errebhi and Wilcox, 1990; Dowling, 1998; Britto and Kronzucker, 2002) and among maize cultivars/hybrids (Bennett et al, 1964; Alföldi et al, 1992; Schortemeyer and Feil, 1996; Schortemeyer et al, 1997) in actual visible toxicity symptoms can differ substantially (Bennett et al, 1964; Bennett and Adams, 1970; Colliver and Welch, 1970b; Creamer and Fox, 1980; Errebhi and Wilcox, 1990; Alföldi et al, 1992; Schortemeyer and Feil, 1996; Dowling, 1998).…”
mentioning
confidence: 99%
“…As interações entre cultivares de milho e bactérias fixadoras de N e/ou promotoras de crescimento são dependentes de especificidades na interação entre genótipos da planta e estirpes dos microrganismos envolvidos (ALFOLDI; PINTER; FEIL, 1992;gARCIA DE SALOMONE;DöBEREINER, 1996;MACHADO et al, 2001). O insucesso no crescimento e teor de N encontrado na maioria dos genótipos de milho submetidos à inoculação com Herbaspirillum seropedicae (ZAE 94) confirma a situação de baixa interação entre os simbiontes, pois menos de 20% dos genótipos avaliados foram responsivos à inoculação.…”
Section: Resultsunclassified